WhatsApp: The Contribution of a Smartphone-Based Applicatio as Media during Online Learning - Umi Rahmawati (Universitas Muhammadiyah Prof. DR. HAMKA, 2020)
E-learning is based on computer learning that is connected to the internet where the users have an opportunity to learn anywhere and anytime. This type of learning become very popular recently, during Covid19. One of the most popular media to use is WhatsApp, the most popular Smartphone-based application. This study aims to describe students' perception regarding the use of WhatsApp as a Learning Media in SMK Nusantara Blora, Central Java. The questionnaire was used as a method for collecting students' data. This research uses descriptive qualitative in elaborating the result and discussion. In this article, the result draws how students interest in having e-learning as a medium of teaching especially in English class.